El bienestar psicológico y COVID 19 en estudiantes universitarios - Portilla Villarreal, Jefferson; Casa Vera, Paola; León Ron, Veronica; Pabón, Karina; Narváez Olmedo, Gabriela (Revista Ecos de la Academia, 2023)
The study seeks to identify the effects that the COVID 19 pandemic had on the psychological well-being of the university population. A quantitative approach of descriptive design was taken, of a cross-sectional type, 2083 students at the Technical University of the North participated, of which 722 belong to the male gender and 1361 to the female, were evaluated with the Ryff Psychological Well-being Scale, which consists of 39 items distributed in 6 dimensions. The data obtained were analyzed with the SPSS Software. It was found that the largest number of students have a high psychological well-being, with men showing an average of 123.40 as opposed to an average of 119.36 in women with a maximum score of 174. In the dimensions, autonomy was ranked as the best scored by students and self-acceptance the lowest scored. The results indicate that a large percentage of students did not have profound effects on mental health due to the confinement owing to the pandemic, but the female gender showed greater affectation and the two genders-maintained strengths mainly related to autonomy.
Keywords: psychological well-being, pandemic, COVID 19, confinement, university students.